Isolation, characterization, and identification of potential Diuron-degrading bacteria from surface sediments of Port Klang, Malaysia - Hanapiah, Munirah; Zulkifli, Syaizwan Zahmir; Mustafa, Muskhazli; Mohamat Yusuff, Ferdaus; Ismail, Ahmad (Elsevier, 2018)
Diuron is an alternative biocide suggested to replace organotin in formulating antifouling paints to be applied on water-going vessels hull. However, it is potentially harmful to various non-targeted marine organisms due to its toxic properties. Present study aimed to isolate, screen and identify the potential of Diuron-degrading bacteria collected from the marine sediments of Port Klang, Malaysia. Preliminary screening was conducted by exposing isolated bacteria to 430 ng/L (background level), followed by 600 ng/L and 1000 ng/L of Diuron concentrations. Nine bacteria colonies survived the exposure of the above concentrations. However, only two strains can tolerate to survive up to 1000 μg/L, which were then characterised and identified using phenotypic tests and the standard 16S rRNA molecular identification. The strains were identified as Comamonas jiangduensis SZZ 10 and Bacillus aerius SZZ 19 (GenBank accession numbers: KU942479 and KU942480, respectively). Both strains have the potential of Diuron biodegradation for future use.